2020
DOI: 10.1002/path.5398
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal papillary neoplasms of the bile duct consist of two distinct types specifically associated with clinicopathological features and molecular phenotypes

Abstract: Intraductal papillary neoplasm of the bile duct (IPNB) is a grossly visible papillary biliary neoplasm with morphological variations and occasional invasion. Recently a new classification of IPNB into type 1 and type 2 was proposed in which the type 1 IPNBs consist of fine papillary neoplastic glands and the type 2 IPNBs consist of complex branching glands, seldom with foci of solid-tubular components. However, clinicopathological and molecular characteristics of these types of IPNBs are yet to be identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 26 publications
1
50
0
Order By: Relevance
“…Some patients may present with mucus hypersecretion. Like intraductal papillary mucinous neoplasm (IPMN) of the pancreas, IPNB is histologically classified into four types based on their histological and immunohistochemical features: pancreaticobiliary (Figure 6C ), intestinal, gastric and oncocytic types[ 67 ]. Pancreaticobiliary and intestinal subtypes are the most common types, although its frequency varies across geographical regions.…”
Section: Precursors Lesions Of Cholangiocarcinomamentioning
confidence: 99%
“…Some patients may present with mucus hypersecretion. Like intraductal papillary mucinous neoplasm (IPMN) of the pancreas, IPNB is histologically classified into four types based on their histological and immunohistochemical features: pancreaticobiliary (Figure 6C ), intestinal, gastric and oncocytic types[ 67 ]. Pancreaticobiliary and intestinal subtypes are the most common types, although its frequency varies across geographical regions.…”
Section: Precursors Lesions Of Cholangiocarcinomamentioning
confidence: 99%
“…The diagnosis of IPNB must be descriptive because it is determined using the papillary morphology in both humans and mice. Two reports have identified genetic alterations in human IPNBs using next-generation sequencing analysis (Aoki et al, 2020;Yang et al, 2019). The frequently found genetic mutations included TP53, KRAS, GNAS, and RNF43; however, none exceeded 50%.…”
Section: Discussionmentioning
confidence: 99%
“…CTNNB1 is an important constituent gene in the Wnt/β-catenin pathway. Although the Wnt pathway is known to be activated in bile-duct cancers, CTNNB1 mutation is not commonly reported in patients with cholangiocarcinoma and IPNB [ 3 , 6 ]. Moreover, genetic mutation in CTNNB1 is involved in the formation of pyloric-gland polyps in the stomach and gall bladder [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some whole-exome sequencing-based studies on bile-duct cancers have been reported, and KRAS and TP53 are listed as important gene variants, most analyses were performed in mixed patients with IPNB and bile-duct cancers [ 5 ]. Aoki et al recently performed targeted capture sequencing of cancer-driver genes in the context of IPNB [ 3 ]; however IPNB-specific gene mutations could not be identified via target gene analysis alone. In the present case, whole-exome sequencing of the tumor revealed somatic mutations in well-known cancer-driver genes such as CTNNB1 and NFE2L2 ; interestingly, mutations frequently identified in bile-duct cancers and IPNB, such as KRAS and GNAS mutations, were not found ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation